THE STRENGTH AND CREEP OF FROZEN SOILS AND CALCULATIONS FOR ICE-SOIL RETAINING STRUCTURES (PROCHNOST' I POLZUCHEST' MERZLYKH GRUNTOV I RASCHETY LEDOGRUNTOVYKH OGRAZHDENII) - Vialov, S. S.; Gmoshinskii, V. G.; Gorodetskii, S. E.; Grigorieva, V. G.; Zaretskii, Iu. K. (1965)
Contents: Mechanism of Rheological Processes; Principles of Calculation for the Creep and Long-Term Strength of Frozen Soils; Cryogenous Texture and Strength of Frozen Soils; Methods for Testing Frozen Soils in Creep and for Long-Term Strength; Experimental Study of the Creep of Frozen Soils; Experimental Study of the Long-Term Strength of Frozen Soils; Calculations for Strength and Creep of Mine Shaft Retaining Structures Sunk by Means of the Freezing Process; Models of Ice-Soil Cylinders; and Comparison of the Analytical Solutions with Model Results, and Recommend Formulae for Calculations.